Appraising the counterpoint : bifocal readings of literary landscapes in the American Renaissance and post-apartheid South Africa - Theron, Cleo Beth (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.